PERBEDAAN PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN TIPE JIGSAW TERHADAP HASIL BELAJAR FISIKA DITINJAU DARI MOTIVASI BELAJAR SISWA - Aris Doyan; Wayan Gunada; Susilawati -; Ida AYu Desy Adriani (Jurnal Penelitian Pendidikan IPA, 2015)
The research is aimed to finding difference of effect the implementation of cooperative learning model STAD and Jigsaw type on the result of physic learning, difference of effect the students whose achievement motivation on result of physic learning and interaction of effect between the learning model implementation and the achievement motivation on the result of physic learning. This type of research is quasi experimental with Factorial Design of 2x2. The population in this research is all Class VIII SMPN 12 Mataram with used technique cluster random sampling. There are two samples that are class VIII C as an experiment class I and class VIII D as experiment class II. The experiment class I used the treatment STAD cooperative learning model and the experiment class II used the treatment Jigsaw cooperative learning. Analysis technique using analysis of variance (ANOVA) two way different cells. Based on by calculation hypothesis testing obtained that, FA hint (6,37) > Ftable (4,02) then Ho1 rejected, FB hint (12,37) > Ftable (4,02) then Ho2 rejected,, FAB hint (0,96) < Ftable (4,02) then Ho3accepted. With significant level 0,05 obtained that there is a difference of effect the implementation of cooperative learning model STAD and Jigsaw type on the result of physic learning, there is a difference of effect the students whose achievement is high and low motivation on the result of physic learning and there is no interaction between of cooperative learning model STAD and Jigsaw type with achievement motivation towards of physics learning.